2015
DOI: 10.1016/j.jelekin.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Young individuals with a more ankle-steered proprioceptive control strategy may develop mild non-specific low back pain

Abstract: Altered proprioceptive postural control has been demonstrated in people with non-specific low back pain (LBP). However, the cause-effect relation remains unclear. Therefore, more prospective studies are necessary. Proprioceptive postural control of 104 subjects was evaluated at baseline using a force plate and with application of vibration stimulation on ankle and back muscles. Spinal postural angles were measured with digital photographs. Psychosocial variables and physical activity were registered using ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 35 publications
1
57
0
1
Order By: Relevance
“…This might be obvious because the questionnaire is especially developed for individuals 'with' LBP (for which the internal consistency was found to be sufficient) and not for those without. As item 4, 5 and 6 are specifically related to lumbar proprioceptive acuity, we recommend further studies to further reveal potential independence of this feature, for example by use of local muscle vibration (Brumagne et al, 2000;Brumagne et al, 2008;Claeys et al, 2011;Claeys et al, 2015). Also, we recommend future studies to perform a confirmatory factor analysis as there are only few language versions of the FreBAQ available at this point (English and Japanese).…”
Section: Discussionmentioning
confidence: 99%
“…This might be obvious because the questionnaire is especially developed for individuals 'with' LBP (for which the internal consistency was found to be sufficient) and not for those without. As item 4, 5 and 6 are specifically related to lumbar proprioceptive acuity, we recommend further studies to further reveal potential independence of this feature, for example by use of local muscle vibration (Brumagne et al, 2000;Brumagne et al, 2008;Claeys et al, 2011;Claeys et al, 2015). Also, we recommend future studies to perform a confirmatory factor analysis as there are only few language versions of the FreBAQ available at this point (English and Japanese).…”
Section: Discussionmentioning
confidence: 99%
“…1): transmuscular surgery + physiotherapy (n = 6), transmuscular surgery + usual care (n = 6), paramedian surgery + physiotherapy (n = 6), and paramedian surgery + usual care (n = 7). These groups were clustered by a mixed group design because power analysis (Brumagne et al, 2008;Claeys et al, 2011Claeys et al, , 2012Claeys et al, , 2015Janssens et al, 2015) revealed a sample size of 11 participants to provide adequate power (0.80 with a two-tailed alpha level of 0.05) to detect a clinically relevant difference in center of pressure displacement on unstable support surface (our primary outcome measure with smallest effect size). First, they were randomly allocated (blinded by computer algorithm) for surgical approach into a transmuscular group (n = 12; 7 women/5 men) and paramedian group (n = 13; 7 women/6 men).…”
Section: Participantsmentioning
confidence: 99%
“…The amount of this center of pressure displacement represents the extent to which an individual makes use of the proprioceptive signals of the vibrated muscles to maintain the upright posture. Muscle vibrators (Maxon motors, Switzerland) were applied bilaterally over the triceps surae ('ankle') muscles and lumbar paraspinal ('back') muscles, as studied previously (Brumagne et al, 2008;Claeys et al, 2011Claeys et al, , 2012Claeys et al, , 2015Janssens et al, 2015). Participants were instructed to stand barefoot on the force plate, with their arms relaxed along the body and occluded vision.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations